Predictors of in-hospital mortality in primary intracerebral haemorrhage in East coast of Peninsular Malaysia - Rathor, Mohammad Yousuf; Abdul Rani, Mohammed Fauzi; Ab Rahman, Jamalludin; How, Soon Hin; Abdul Rashid, Mohd Amran; Che Abdullah, Shahrin Tarmizi; Omar, Ahmad Marzuki; Shah, Anis (Neurology Asia, 2012)
Background and Objectives: Despite much medical progress, stroke remains a leading cause of death and disability. The aim of our study was to analyze the frequency of various risk factors and determine predictors of in-hospital mortality among primary intracerebral hemorrhage (PICH) patients, thus providing insight in developing therapeutic strategies to improve the outcome. Methods: A prospective study conducted at a tertiary care hospital. Results: A total of 160 patients (108 male and 52 female) were evaluated. Their ages ranged from 25 to 85 years (mean age was 58.3 ± 11.4 years). Hypertension was the commonest risk factor (74.4%), followed by diabetes mellitus (18.8%) and cigarette smoking (36.3%). The commonest location of ICH was lobar (43.8%) followed by basal ganglia / internal capsule (28.1 %) and multilobar (13.1%). The overall in-hospital mortality was 32.5 %. About one third (32.7%) of the deaths occurred within fi rst 24 hours, this rose to 38.5% within fi rst 2 days and 84.6% within one week. The signifi cant independent predictors of acute in- hospital mortality were Glasgow Coma Scale (GCS) on admission, posterior fossa bleed (OR 11.01; 95% CI 3.21 to 37.81), hematoma volume >60ml (OR 4.72; 95% CI 1.34 to 16.64), mid line shift (OR 3.32; 95% CI 1.05 to 10.50) and intraventricular extension of haemorrhage (OR 5.69; 95% CI 2.24 to 14.47). Conclusion: Low GCS score, posterior fossa bleed, and large hematoma volume were main indicators of mortality following PICH in East coast of Peninsular Malaysia.